SOME ISSUES ON JUDICIAL SUPERVISION OVER THE CONDITIONAL EARLY RELEASE (PAROLE) - Sargsyan, Arpine (State and Law, 2021)
Article is devoted to the judicial supervision over the conditional early release (parole). The author has raised and analyzed some of the key issues related to the subject matter and presented suggestions for their solution: within the framework of the article, the discretionary and mandatory grounds of recalling conditional early release (parole) were discussed.
Keywords: conditional early release (parole); prisoner; judicial supervision; probation